2011
DOI: 10.1111/j.1365-2095.2009.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arachidonic acid supplementation on reproductive performance of tank-domesticated Penaeus monodon

Abstract: The reproductive performance of domesticated Penaeus monodon was assessed when fed on two experimental semi‐moist maturation diets varying in their arachidonic acid content for 21 days before ablation and throughout a 17‐day reproductive assessment. The biochemical composition of the two semi‐moist two diets was similar with the exception of arachidonic acid (ARA) content; the basal diet (BAS) consisting of 0.9 g kg−1 DM ARA (1.1% of total fatty acids) and the supplemented diet (ARA‐SUP) consisting of 5.0 g kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 64 publications
(138 reference statements)
5
36
0
2
Order By: Relevance
“…Notably, the diet fed in the present study contained 10% more MB, which may have made the pelleted diet less palatable overall, reducing uptake of the pelleted maturation diets. In addition, astaxanthin (derived from Carophyll Pink), arachidonic acid (ARASCO ® ) and phospholipids (in the form of krill meal) are known to improve reproductive performance and embryonic and larval development (Alava et al, 1993, Coman et al, 2011, Wouters et al, 2001a, and thus their inclusion within chapter 2's maturation diets may have served to satisfy or offset nutritional requirements which were lacking in the current experiments commercial formulation.…”
Section: However These Results Contrast To the Positive Effects On Rmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, the diet fed in the present study contained 10% more MB, which may have made the pelleted diet less palatable overall, reducing uptake of the pelleted maturation diets. In addition, astaxanthin (derived from Carophyll Pink), arachidonic acid (ARASCO ® ) and phospholipids (in the form of krill meal) are known to improve reproductive performance and embryonic and larval development (Alava et al, 1993, Coman et al, 2011, Wouters et al, 2001a, and thus their inclusion within chapter 2's maturation diets may have served to satisfy or offset nutritional requirements which were lacking in the current experiments commercial formulation.…”
Section: However These Results Contrast To the Positive Effects On Rmentioning
confidence: 99%
“…It is well established that the maturation diet fed immediately prior to spawning can drastically impact on egg quality and thus egg hatching in shrimp (Millamena, 1989, Bray and Lawrence, 1992, Cahu et al, 1995a, Cahu et al, 1994, Xu et al, 1994a, Wouters et al, 2001a, Wouters et al, 1999, Coman et al, 2007a, Coman et al, 2011, Hoa et al, 2009). The proximate analysis demonstrated that the diet containing MB had lower protein content than the control diet.…”
Section: However These Results Contrast To the Positive Effects On Rmentioning
confidence: 99%
See 3 more Smart Citations